Structural and functional stability of foreign genes in transgenic tobacco plants - Vyskot, B; Brzobohatý, B; Karlovská, L; Bezdĕk, M (Folia biologica, 1989)
The Drosophila genomic fragment Dm111 and the selectable dominant nptII gene were transferred via a Ti-vector into tobacco plants in order to check the structural and functional stability of transgenes in plants and their progeny. Southern blot analyses clearly showed that transgenes were integrated intact and did not suffer from any gross DNA rearrangements. Contrary to this structural stability, not all of the transgenic plants and their offspring displayed the original and stable expression of the nptII gene. The levels of the NPTII enzyme strongly varied in individual plants and did not depend on the copy number of the nptII gene. Both the non-stable nptII expression during the individual plant development in one original transgenic tobacco and some irregularities in segregation ratios after self-pollination indicated that epigenetic effects due to methylation of DNA modulated the expression of foreign genes in transgenic plants. This conclusion was supported by a spontaneous and 5-azacytidine-stimulated demethylation.
Keywords: jedovaté rostliny; rostliny; Rhizobium; restrikční enzymy; Phosphotransferases; rekombinantní DNA; hybridizace nukleových kyselin; transfekce; DNA; Transformation, Genetic; Kanamycin; transformace genetická; léková rezistence; DNA, Recombinant; DNA Restriction Enzymes; Cloning, Molecular; Plants; tabák; Escherichia coli; Drosophila; zvířata; kanamycinkinasa; Plants, Toxic; Plasmids; kanamycin; Kanamycin Kinase; Transfection; klonování DNA; Drug Resistance; plazmidy; fosfotransferasy; Nicotiana; Nucleic Acid Hybridization; Animals